A microscopic model for the dielectric function of Ge quantum wires - Alfaro, P.; Vazquez, R.; Lobota, I.; Ramos, A.E.; Cruz-Irisson, M. (Functional Materials, 2005)
Free-standing, infinitely long, and homogeneous quantum wires of square cross section are considered using the chessboard-like supercell model. The optical transition properties of Ge nanocrystals are studied by means of an sp³s* semiempirical tight-binding approximation. The calculations have been carried out for light polarized in the [100] direction, i.e., perpendicular to the wire alignment. Dependence of the imaginary part of the dielectric function on the quantum confinement is presented within two different schemes: intra-atomic and interatomic matrix elements, which are applied and compared. The principal results show that although the intra-atomic matrix elements are small in magni- tude, the interference between these terms and the interatomic matrix elements contrib- utes about 25 % of the total absorption. Thus, it appears that a quantitative treatment of nanostructures may not be possible (in general) without the inclusion of intra-atomic matrix elements.